Tathwir Maddah at-Ta’liim ala Asasi Tatbiq Cap Cut bi Istikhadami Instagram li Thalabah as-Shaf al-Asyir bi al-Madrasah al-Aliyah al-Hukumiyyah Palopo - mangera, sunarti; Kartini; Mubassyirah Bakri (Al Ibrah: Journal of Arabic Language Education, 2022)
Abstract This research aims to determine the development process and level of validity of the product being developed. This type of research is research and development (R&D) by adapting the 4D development model which consists of four stages, namely definition, design, development and dissemination. The subjects of this research were class X students at MAN Palopo. Data collection techniques use observation, interviews, validation sheets, student response questionnaires, and documentation. Data was analyzed using qualitative and quantitative data analysis techniques. The results of this development research are al-hiwayah teaching materials using Instagram based on the Capcut application for class X students at MAN Palopo. The product validation test results show that: 1) material expert validation obtained a score of 98.18%; 2) media expert validation obtained a score of 93.33%; 3) and learning expert validation obtained a score of 92.94%. Based on the results of product validation tests by three expert validators, it shows that al-hiwayah teaching materials using Instagram based on the Capcut application are very valid to be applied in Arabic language learning.   الملخص يهدف هذا البحث إلى تحديد عملية التطوير ومستوى صلاحية المنتج المطور. نوع البحث هو البحث والتطوير (R&D) باستخدام نموذج تطوير D4 الذي يتكون من أربع مراحل وهي مرحلة التحديد، والتصميم، والتطوير، والانتشار. وحدات البحث هم طلبة الصف العاشر بالمدرسة العالية الحكومية فالوفو. وأساليب جمع البيانات المستخدمة هي الملاحظة والمقابلة وأوراق التحقق من الصحة واستبانات استجابة الطلبة والوثائق. وتم تحليل البيانات باستخدام أساليب تحليل البيانات الكيفية والكمية. نتيجة هذا البحث والتطوير هي مادة التعليم على أساس تطبيق CapCut بإستخدام إنستغرام في مادة الهواية لطلبة الصف العاشر بالمدرسة العالية الحكومية فالوفو. نتائج التحقق من صحة المنتج:1) التحقق من الصحة من قبل خبير المادة حصل على درجة 98،18%؛ 2) وخبير الوسيلة حصل على 93،33%؛ 3) وخبير التعليم حصل على 92،94%. بناءً على النتائج، يمكن استنتاج أن وسيلة التعليم المطورة صالحة جداً للتطبيق في تعليم اللغة العربية.